If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(4r + 6) = 8 + -3(-5r + -4) Reorder the terms: 4(6 + 4r) = 8 + -3(-5r + -4) (6 * 4 + 4r * 4) = 8 + -3(-5r + -4) (24 + 16r) = 8 + -3(-5r + -4) Reorder the terms: 24 + 16r = 8 + -3(-4 + -5r) 24 + 16r = 8 + (-4 * -3 + -5r * -3) 24 + 16r = 8 + (12 + 15r) Combine like terms: 8 + 12 = 20 24 + 16r = 20 + 15r Solving 24 + 16r = 20 + 15r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-15r' to each side of the equation. 24 + 16r + -15r = 20 + 15r + -15r Combine like terms: 16r + -15r = 1r 24 + 1r = 20 + 15r + -15r Combine like terms: 15r + -15r = 0 24 + 1r = 20 + 0 24 + 1r = 20 Add '-24' to each side of the equation. 24 + -24 + 1r = 20 + -24 Combine like terms: 24 + -24 = 0 0 + 1r = 20 + -24 1r = 20 + -24 Combine like terms: 20 + -24 = -4 1r = -4 Divide each side by '1'. r = -4 Simplifying r = -4
| 5+2*(x-35)=(5+2)*x-35 | | 2x^2+28x+98=512 | | -55=4x+3x+1 | | 4+2y+7+6y=-13 | | 10x=20-15x | | y^2+y+22=0 | | -43+s=9 | | 10=9x+9 | | 6(3n+2)=9(9n+4)+1 | | 4x+0=8x+4 | | -33-3x=-6-2(1+4x) | | 0=sin^2(x)+cos(x)-0.5 | | -(9x-4y+7z)= | | 4(2d-3)-3d=3d-4 | | 3-(-12x+5)=x | | 0.5x-3.8=0.7 | | (3x+xy-2)-(2xy+x-4)= | | m=6+n | | [4(6-2)-5]-[7-(8-5)]= | | 15y^2+25y^3= | | 2a-6=6a-22 | | 600=(nsquared-n) | | 4h-13=7 | | -[10z-(19z+6)]=6+(8z+4) | | 4x/5-2x/4=11 | | 2(2x-3y)(2x+8y)=0 | | 4(x+8)=17-4x | | 5w+2(1-2w)=-(3-2w) | | 4.7-0.21x=-.37 | | -2x-9=-x-(7+2x) | | 7m+7n-7(6m-9m)= | | 3(2x-7)=-18 |